Models to evaluate the severity of pedestrian-vehicle conflicts in five cities. Issue 2 (29th November 2019) - Tageldin, Ahmed; Sayed, Tarek
ABSTRACT: Previous studies have shown that traditional traffic conflict indicators that depend on time-proximity are not a viable measure of conflicts severity in all driving cultures. Behavior-based indicators that are dependent on road-users evasive actions were shown to better reflect severity in less-organized trafﬁc environments. The objective of this paper is to examine the use of time proximity-based and evasive action-based indicators on pedestrian conflicts in five major cities; Shanghai, New Delhi, New York, Doha, Vancouver. Time-to-collision is used as the primary time proximity indicator. Pedestrian evasive actions are reflected in the sudden variation of pedestrian gait parameters. Ordered-response models were utilized to relate both indicators to severity taking into account the unobserved heterogeneity in conflicts. Results show that the evasive action-based indicator is most effective in less-organized traffic environments such as Shanghai and New Delhi while the time proximity measure was shown effective in more structured environments such as Vancouver.